2018
DOI: 10.5194/amt-2018-206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CALIPSO Lidar Calibration at 532 nm: Version 4 Daytime Algorithm

Abstract: Abstract. The Cloud Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) mission released 10version 4.00 of their lidar level 1 data set in April of 2014, and subsequently updated this to version 4.10 in November of 2016. The primary difference in the newly released version 4 (V4) data is a suite of updated calibration coefficients calculated using substantially revised calibration algorithms. This paper describes the revisions to the V4 daytime calibration procedure for the 532 nm parallel c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

7
2

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
(23 reference statements)
2
17
0
Order By: Relevance
“…Here, the resulting cloud mask using the improved hydrometeor detection from G17 (described below as the G17 version) is compared with the operational CloudSat R04 and R05 version cloud masks, which are stored in level 2B GEOPROF data products. Following M08, we use the CALIPSO version 4 lidar vertical feature mask (VFM) (Getzewich et al, ; Vaughan et al, ) as a reference to evaluate hydrometeor detection algorithm, because the lidar is more sensitive to thin cloud than the radar. For most of their operational life (and for all the data examined here), CALIPSO and CloudSat were both parts of the A‐Train satellite constellation.…”
Section: Methodsmentioning
confidence: 99%
“…Here, the resulting cloud mask using the improved hydrometeor detection from G17 (described below as the G17 version) is compared with the operational CloudSat R04 and R05 version cloud masks, which are stored in level 2B GEOPROF data products. Following M08, we use the CALIPSO version 4 lidar vertical feature mask (VFM) (Getzewich et al, ; Vaughan et al, ) as a reference to evaluate hydrometeor detection algorithm, because the lidar is more sensitive to thin cloud than the radar. For most of their operational life (and for all the data examined here), CALIPSO and CloudSat were both parts of the A‐Train satellite constellation.…”
Section: Methodsmentioning
confidence: 99%
“…The improved calibration coefficients in V4 facilitated the detection of optically thinner layers than were detected in V3 Getzewich et al, 2018). A side effect of this improvement is an increased occurrence of optically-thin layers detected along the tenuous edges of ice clouds.…”
Section: Fringesmentioning
confidence: 97%
“…Recent studies have found higher lidar ratios for volcanic ash (Table 3). For example, lidar ratios of 50 ± 10 sr were retrieved for volcanic ash transported over Europe during the April 2010 Eyjafjallajökull volcano eruption Groß et al, 2012), with mean lidar ratios of 60 ± 5 sr at Leipzig on 16 April 2010 . Recently, Prata et al (2017) used constrained CALIOP retrievals to estimate mean particulate lidar ratios of 69 ± 13 sr for volcanic ash from the June 2011 Puyehue-Cordón Caulle eruption.…”
Section: Volcanic Ashmentioning
confidence: 99%